From genomic insights to public health impact: opportunities, challenges, and future directions in personalized disease prevention - Ayinde, Mujahideen Oluwadare; Temilola, Kadiri Khairat; Dangana, Amos; Koshechkin, Konstatin; Raheem, Muqadas (International Journal Of Community Medicine And Public Health, 2025)
Genomic science is rapidly reshaping healthcare, offering unprecedented opportunities to prevent disease through precision approaches. When combined with traditional public health strategies, genomic data can enable earlier detection, refined risk stratification, and more targeted interventions, a vision often described as precision public health. Despite this promise, real-world integration remains limited. Methodological challenges such as ancestry bias, outcome heterogeneity, and inconsistent study designs undermine generalizability. Technical barriers, including fragmented data systems and poor interoperability, restrict scalability. Ethical concerns around privacy, equity, and governance further complicate implementation, particularly in resource-limited settings. This narrative review synthesizes current applications of genomic public health integration, including polygenic risk scores (PRS), infectious disease surveillance, and digital health initiatives. It highlights key opportunities for enhancing personalized disease prevention while critically examining persistent methodological, technical, and ethical barriers. Future progress will depend on diverse population inclusion, methodological standardization, interoperable infrastructures, and robust ethical frameworks. By addressing these gaps, genomic insights can move from research settings to scalable, equitable public health impact.